3-(2-Bromoacetyl)-6-fluoro-2H-chromen-2-one - H. N. HarishKumar; Sudarshan Mahapatra; K. N. Venugopala; Kittappa Mariswamy Mahadevan (Acta Crystallographica Section E, 2011)
The non-H atoms of the title compound, C11H6BrFO3, are essentially coplanar (r.m.s. deviation for all non-H atoms = 0.074 Å). In the crystal, the molecules are linked by C—H...O and C—H...Br interactions.